Tools of the enterprise logistics processes optimizing - Pavliuk, Tetiana; Polusmiak, Yuliia; Onopriienko, Iryna; Potapenko, Andrii (Management and Entrepreneurship: Trends of Development, 2024)
The article reveals the essence and expediency of the process approach applying for effective enterprise management in conditions of martial law in the country, analyzes various scientific approaches to the «logistics process» concept definition, provides the logistics processes classification and its main characteristics. It was recapped that a common thing for various scientific points of view on the logistics process essence definition are: logistics process clear structure presence, its connection with time and consumer-oriented direction. As a result of analysis of different scientific approaches to logistics processes classification, basic and auxiliary logistics processes were identified.The scale of destructive impact of Russian Federation full-scale military intrusion on the territory of Ukraine on the national logistics state was analyzed, and the key factors that allowed Ukrainian business to increase sustainability of trade logistics after the start of the full-scale invasion were determined.Based on the analysis of the enterprise's logistics system functional structure, it was determined that the search for ways to improve the enterprise's functioning efficiency requires the acceptance of the cohesion of all logistics processes within the logistics system and the bonds between the enterprise's logistics system and its external environment. It was claimed that the crucial background for achieving of the potential reserve of the enterprise overall efficiency growth is the applying of optimizing logistics processes strategy. The key goals and tasks of logistics processes optimization were formulated. The main tools of logistics processes optimizing at the enterprise were analyzed.JEL Classification: С61, M13